2021
DOI: 10.21037/atm-21-2247
|View full text |Cite
|
Sign up to set email alerts
|

SLC7A5 serves as a prognostic factor of breast cancer and promotes cell proliferation through activating AKT/mTORC1 signaling pathway

et al.

Abstract: Background: The purpose of our research was to determine if the clinical, pathological, and prognostic functions of SLC7A5 are the same as those of other molecular breast cancer (BC) subgroups. Methods:We used the Oncomine and The Cancer Genome Atlas (TCGA) online databases to examine the expression and genetic changes of SLC7A5 in BC tissues. Immunohistochemical analysis was used to validate the SLC7A5 protein expression in subtypes of BC, while Kaplan-Meier figures and log-rank tests were used to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…SLC7A5 (solute carrier family 7 member 5 or LAT1) is a transporter of large branched-chain and aromatic neutral amino acids [25,26] and is highly expressed in breast cancer, non-Hodgkin's lymphoma and colorectal cancer and positively associated with poor prognoses [27][28][29]. Moreover, SLC7A5 can promote cancer proliferation via AKT/mTORC1 pathway activation [30]. Furthermore, SLC7A5 is a candidate molecular target for cancer therapeutics and inhibition of transport with JPH203 (Nanvuranlat) significantly suppressed the proliferation of estrogen deprivation-resistant (EDR) breast carcinoma cell lines [31].…”
Section: Introductionmentioning
confidence: 99%
“…SLC7A5 (solute carrier family 7 member 5 or LAT1) is a transporter of large branched-chain and aromatic neutral amino acids [25,26] and is highly expressed in breast cancer, non-Hodgkin's lymphoma and colorectal cancer and positively associated with poor prognoses [27][28][29]. Moreover, SLC7A5 can promote cancer proliferation via AKT/mTORC1 pathway activation [30]. Furthermore, SLC7A5 is a candidate molecular target for cancer therapeutics and inhibition of transport with JPH203 (Nanvuranlat) significantly suppressed the proliferation of estrogen deprivation-resistant (EDR) breast carcinoma cell lines [31].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the AKT/mTOR signalling pathway is associated with the transportation of amino acids including leucine by SLC7A5. The overexpression of this protein could elevate the levels of p-AKT and p-mTOR, and thus promote cell proliferation [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Previous studies found that SLC7A5 is overexpressed in a variety of cancers and plays a role in proliferation and metastasis. [27][28][29] Liu et al demonstrated that SLC7A5-mediated L amino acid transport system is essential for the proliferation and survival of vascular smooth muscle cell (VSMC). 30 Notably, increased strain of the blood vessel wall and vascular injury can induce arterial remodeling by stimulating the proliferation of VSMC.…”
Section: Discussionmentioning
confidence: 99%